2013
DOI: 10.1007/s00134-013-3006-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased MerTK expression in circulating innate immune cells of patients with septic shock

Abstract: MerTK expression in circulating innate immune cells is increased in patients with septic shock in comparison with healthy volunteers and trauma patients. Persistent MerTK overexpression after septic shock is associated with adverse outcome. The role of this family of receptors in the pathophysiology of injury-induced immune dysfunctions deserves to be specifically investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Patients who received macrolides more often had chronic obstructive pulmonary diseases. Length of ICU stay in survivors was not significantly different in patients who received macrolides compared to patients who did not [10][11][12][13][14][15][16][17][18][19][20] vs. [10][11][12][13][14][15][16][17][18][19][20], p = 0.9]. ICU mortality was 24.1 % (n = 177).…”
Section: Community-acquired Pneumoniamentioning
confidence: 92%
See 1 more Smart Citation
“…Patients who received macrolides more often had chronic obstructive pulmonary diseases. Length of ICU stay in survivors was not significantly different in patients who received macrolides compared to patients who did not [10][11][12][13][14][15][16][17][18][19][20] vs. [10][11][12][13][14][15][16][17][18][19][20], p = 0.9]. ICU mortality was 24.1 % (n = 177).…”
Section: Community-acquired Pneumoniamentioning
confidence: 92%
“…MerTK is a protein tyrosine kinase that with Tyro-3 and Axl comprises the TAM receptor family. In their very interesting and elegant study, Guignant et al [10] prospectively evaluated 98 patients with septic shock and severe trauma to investigate the expression patterns of TAM receptors in circulating white blood cells. They observed that the evolution of MerTK expression in circulating monocytes over time is associated with adverse outcome in patients with septic shock.…”
Section: Immune Dysfunction During Sepsis and Antimicrobial Dose Varimentioning
confidence: 99%
“…Although inhibition of innate inflammation is essential to prevent autoimmunity during apoptotic cell clearance, prolonged engagement of TAM receptors may cause a state of unresponsiveness in antigen presenting cells required to clear pathogenic micro-organisms. To support this hypothesis, elevated GAS-6 plasma levels are observed in patients with severe sepsis [41,42], and MerTK is elevated on monocytes from patients with septic shock, and is linked to an adverse outcome [43]. The consequences of these observations remain as yet unexplored.…”
Section: Mechanisms Of Susceptibility To Infectionsmentioning
confidence: 99%
“…Monocytes expressing MERTK bore enhanced migratory capacity and hence accumulated in diverse sites of inflammation, that is, liver, lymph nodes, the peritoneum and the circulatory compartment [26]. MERTK has also been found activated in nonhepatic conditions of prolonged anti-inflammatory responses such as septic shock [29].…”
Section: Infection Related Mortality In Acute-on-chronic Liver Failurementioning
confidence: 99%